2023
DOI: 10.1111/cns.14349
|View full text |Cite
|
Sign up to set email alerts
|

White matter structural topologic efficiency predicts individual resistance to sleep deprivation

Fan Guo,
Tian Zhang,
Chen Wang
et al.

Abstract: BackgroundSleep deprivation (SD) is commonplace in modern society and there are large individual differences in the vulnerability to SD. We aim to identify the structural network differences based on diffusion tensor imaging (DTI) that contribute to the individual different vulnerability to SD.MethodsThe number of psychomotor vigilance task (PVT) lapses was used to classify 49 healthy subjects on the basis of whether they were vulnerable or resistant to SD. DTI and graph theory approaches were used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…These findings are congruent with an emerging consensus that structural brain changes are integral to the non‐motor manifestations of PD 54,55 . Our research supports the idea that primary insomnia and sleep deprivation are linked to alterations in critical brain regions that govern emotional regulation, including the amygdala, prefrontal cortex, hippocampus, FG, and ITG 56–61 . The FG and ITG, as our mediation analysis suggests, are pivotal in the nexus between sleep quality and anxiety in A‐PD patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are congruent with an emerging consensus that structural brain changes are integral to the non‐motor manifestations of PD 54,55 . Our research supports the idea that primary insomnia and sleep deprivation are linked to alterations in critical brain regions that govern emotional regulation, including the amygdala, prefrontal cortex, hippocampus, FG, and ITG 56–61 . The FG and ITG, as our mediation analysis suggests, are pivotal in the nexus between sleep quality and anxiety in A‐PD patients.…”
Section: Discussionsupporting
confidence: 89%
“…54,55 Our research supports the idea that primary insomnia and sleep deprivation are linked to alterations in critical brain regions that govern emotional regulation, including the amygdala, prefrontal cortex, hippocampus, FG, and ITG. [56][57][58][59][60][61] The FG and ITG, as our mediation analysis suggests, are pivotal in the nexus between sleep quality and anxiety in A-PD patients. The ramifications of our findings are significant: they contribute to the neurobiological framework of A-PD and imply that interventions focused on enhancing sleep quality may be a viable approach for mitigating anxiety symptoms.…”
Section: Implications For Pd Pathologymentioning
confidence: 99%
“…In fact, greater white matter integrity facilitates efficient signal communication between frontal and parietal regions, potentially conferring enhanced resistance to sleep deprivation (24). Recent studies further affirm that the integrity of the SLF, along with the topological efficiency of the white matter network that includes frontal and parietal tracts, plays a pivotal role in individual variability in sleep deprivation resistance (14,24). Moreover, research focusing on mild cognitive impairment (MCI) has also suggested that elevated FPN activity is linked with both improved sleep quality and enhanced cognitive performance (25).…”
Section: Discussionmentioning
confidence: 97%
“…The PVT was chosen because it provides a direct, objective, and reliable measure of sustained attention, separate from other cognitive functions. Its simplicity, real-world relevance, and adaptability make it particularly useful for research into the factors that can impair or enhance human alertness and attentional performance ( 14 ). During the test, red dots were displayed on a screen, and participants were instructed to respond as rapidly as possible by pressing a designated key on the keyboard when the red dots appeared.…”
Section: Methodsmentioning
confidence: 99%